Narcissistic Behavior and Subjective Well-Being A Study in Emerging Adulthood Instagram Users - Rizq, Attaya Rana; Prihastuty, Rahmawati (Universitas Negeri Semarang, 2025)
This study aims to determine the relationship between narcissistic behavior and subjective well-being in emerging adulthood Instagram users. The method used in this research is quantitative with Pearson Product-Moment correlational analysis. The sampling technique used non-probability sampling technique with incidental sampling technique. The data collection method was carried out by distributing questionnaires online. The subjects of this study amounted to 115 emerging adulthood Instagram users. The data in this study were obtained with The Narcissistic Admiration and Rivalry Questionnaire (NARQ) scale, The Satisfaction With Life Scale (SWLS) scale, and The Scale of Positive and Negative Experience (SPANE) scale. The results of this study indicate that the correlation coefficient (r) value is 0.107 and the significance value is 0.107. (p) is 0.253 where the value is greater than the specified significance level of 0.05. So it can be concluded that narcissistic behavior does not have a significant relationship with subjective well-being in emerging adulthood Instagram users. Thus, the alternative hypothesis or Ha in this study is rejected.